Role of ABCB1 C3435T variant in response to antiepileptic drugs in epilepsy: a review - Haerian, B.S.; Mohamed, Z.; Mohamed, E.H.M.; Lim, K.S.; Tan, H.J.; Tan, C.T.; Raymond, A.A. (2009)
Over-expression of P-glycoprotein (P-gp), the encoded product of the ATP-binding cassette (ABC), sub-family B, member 1 (ABCB1/MDR1) gene, plays an important role in mediating multidrug resistance to antiepileptic drugs (AEDs) in about 30 of patients with epilepsy. Genetic variation may in part explain inter-individual differences in phenotype-genotype relationships in the pharmacological response of epilepsy patients to AEDs. The synonymous C3435T polymorphism is one of the most common allelic variants in the ABCB1/MDR1 gene, proposed in the causation of refractory epilepsy. Many studies have shown the relationship between C3435T polymorphism and refractoriness to AEDs in epilepsy. However, there is controversy between the findings of various studies, that is, whether ABCB1/MDR1 C3435T gene polymorphism is associated with response to AEDs in epilepsy patients. This review provides a background and discusses the results of investigations on possible confounding factors affecting the interpretation and implementation of association studies in this area.